ПЛАКЕТИ И ЗНАЧКИ НА ОПШТОНАРОДНАТА ОДБРАНА НА СОЦИЈАЛИСТИЧКА РЕПУБЛИКА МАКЕДОНИЈА - PLAQUES, BADGES AND PINS OF THE TOTAL PEOPLE’S DEFENSE OF THE SOCIALIST REPUBLIC OF MACEDONIA - Trajce Trajkov (Македонски хералд - Macedonian Herald, 2020)
The article deals with an important but lesser known topic in Macedonian phaleristic studies—the award system of the Total Peoples Defense of the Socialist Republic of Macedonia (TPD of SRM). Based on the collection material and citation of the legal regulations from the three Decisions adopted by the Presidency of the SRM in 1976, 1983, and 1984, recognitions (pins, plaques, and commendations) and awards of the TPD of SRM are presented in photographs and described in detail. Illustrations show the gold, silver, and bronze pins of the TPD of 1976, the badege and the silver plaque of the TPD of 1984, the pins of the Republic’s campaign “All-In Defense and Protection (SVOZ)”, as well as the commendation of 1982 awarded by the commander of the Republic headquarters of the TDP of SRM. These were granted according to strictly prescribed criteria and can rightly be considered the first Macedonian state military decorations.